CORRELATION BETWEEN ANEMIA AND THE INCIDENCE OF DYSMENORRHEA IN ADOLESCENT GIRLS - Faizah Hasnia; Rize Budi Amalia; Lestari Sudaryanti; Jimmy Yanuar Annas (Indonesian Midwifery and Health Sciences Journal)
Abstract